Business history around the world - Amatori, Franco; Jones, Geoffrey (Cambridge, UK ; New York : Cambridge University Press, 2003)
This book offers the first in-depth international survey of current research and debates in business history. Historians here document and analyze the evolution of a wide range of important companies, their patterns of innovation, production, and distribution, their financial affairs, their political activities, and their social impact.
Cover; Half-title; Series-title; Title; Copyright; Contents; Acknowledgments; Contributors; 1 Introduction; 2 Identity and the Boundaries of Business History; 3 Understanding Innovative Enterprise; 4 Productive Alternatives; 5 Business History in the United States at the End of the Twentieth Century; 6 British and Dutch Business History; 7 Scandinavian Business History at the End of the 1990s; 8 Business History in German-Speaking States at the End of the Century; 9 Business History in France; 10 Business History in Italy at the Turn of the Century; 11 Business History in Spain.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Economic history -- 1990-; Business -- History; Industrial organization -- Cross-cultural studies; Histoire économique -- 1990-; Affaires -- Histoire; Industrie -- Organisation, contrôle, etc. -- Études transculturelles; BUSINESS & ECONOMICS -- Industries -- General; Business; Economic history; Industrial organization; Wirtschaft; Kulturvergleich; Since 1990; Electronic books; Cross-cultural studies; History